Factor analysis of ad liking and prediction of purchase intent through emotionomics - Toma, Syeda Tanzina Farhin; Bhuiyan, Shahan Jamil; Dawood, Tahmid; Saha, Chandan Kumar (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2019.